Preparation And Charactrisation Of Tramadol Microspheres For Post-Operative Pain - Bhanupriya, B (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Tramadol is a centrally acting opioid analgesic mainly used for post-operative pain with the absence of clinical relevant cardiovascular or respiratory side effects. It has a short half-life of 3-5hrs. Due to their short half-life they need to be administered frequently. For the sustained delivery of Tramadol, microspheres containing Polycaprolactone (PCL) and Polyvinylpyrrolidone (PVP) in different ratios were prepared by o/o solvent evaporation method using Span 20 and span 80 as surfactants. Encapsulation efficiency and drug loading of microspheres increased with decrease in concentration of emulsifying agent. The encapsulation efficiency and drug loading of the microspheres increased with increase in PVP concentration due to affinity between the drug and the hydrophilic polymer. The particle size increases with increase in the HLB values of the surfactants used. SEM (Scanning electron microscope) revealed microspheres were discrete, spherical. FTIR of pure and encapsulated drug in all formulation showed no significant difference in characteristic peaks, suggesting stability of tramadol during encapsulation process. Rapid drug release was observed in microspheres with higher concentration of PVP (polyvinylpyrrolidone), PVP acts as channeling agent.